2005
DOI: 10.1088/0953-8984/17/3/011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of1H–14N polarization transfer experiments in molecular crystals

Abstract: A general theoretical description of polarization transfer processes in multi-spin systems containing dipole as well as quadrupole spins is formulated on the background of the Liouville–von Neumann equation. The density operator formalism is used to describe the evolution of an arbitrary spin system due to quadrupole, Zeeman and dipole–dipole interactions. This approach is applied to interpret previously published 1H–14N cross-relaxation NMR experiments for measuring the 14N quadrupole coupling constants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…One of them is related to polarization transfer effects [24][25][26][27] between protons and Br nuclei. Polarization transfer can occur in systems containing nuclei of the spin quantum number 1/2 mutually coupled to nuclei possessing quadrupole moments.…”
Section: H Nmr Relaxation Studiesmentioning
confidence: 99%
“…One of them is related to polarization transfer effects [24][25][26][27] between protons and Br nuclei. Polarization transfer can occur in systems containing nuclei of the spin quantum number 1/2 mutually coupled to nuclei possessing quadrupole moments.…”
Section: H Nmr Relaxation Studiesmentioning
confidence: 99%
“…One of the first articles demonstrating this effect is dealing with powdery polyvinylchloride containing 35 Cl and 37 Cl nuclei (I = 3/2) [12]. Also, studies on solids containing 14 N [16,17] were reported. Cases were presented, where 14 N (I = 1) nuclei produce QRE peaks in the NMRD profile of biological systems, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The contributions to the 1 H spin-lattice relaxation caused by 1 H-X (X = 14 N, Bi, Br) dipoledipole interactions can lead to an effect referred to as quadrupole relaxation enhancement ("quadrupole peaks"). [31][32][33][34][35] H-X contribution to the overall relaxation is almost negligible, except for the frequencies at which the "quadrupole peaks" appear. [10,36] This effect is as ource of information on the timescale of molecular dynamics and molecular arrangement (structure) around the quadrupole nucleus, as the positions of the peaks depend on the electric field gradient at the position of this nucleus.…”
Section: Theorymentioning
confidence: 96%